Imagine Me : visualising your identity - Lisa den Teuling, ....-; BIS Publishers; Studio Lisa (Amsterdam : BIS Publishers, 2020)
How would you describe yourself or another person? Have you ever wondered how your identity could be visualised? It’s not that easy, right? Imagine Me enables you to talk about the complicated and intimate subject of identity in a playful and accessible manner. Instead of using words and questions, you use visualisations to start a meaningful conversation about identity. The game consist out of 99 cards, each card has an authentic illustration that represents a particular trait. The cards are divided into three groups; Personality Traits, Character Traits and Colour Traits. The goal of this game is to compile and build a collage consisting out of 7 cards that represent your, or someone else’s Visual Identity. From 12+ years. From 1 to 99 players. 4 game variants.
Keywords: Board game; Card game; Gezelschapsspel